SLAM Associated Protein Signaling in T Cells: Tilting the Balance Toward Autoimmunity - Gartshteyn, Yevgeniya; Askanase, Anca D.; Mor, Adam (Frontiers in Immunology, 2021)
T cell activation is the result of the integration of signals across the T cell receptor and adjacent co-receptors. The signaling lymphocyte activation molecules (SLAM) family are transmembrane co-receptors that modulate antigen driven T cell responses. Signal transduction downstream of the SLAM receptor is mediated by the adaptor protein SLAM Associated Protein (SAP), a small intracellular protein with a single SH2 binding domain that can recruit tyrosine kinases as well as shield phosphorylated sites from dephosphorylation. Balanced SLAM-SAP signaling within T cells is required for healthy immunity, with deficiency or overexpression prompting autoimmune diseases. Better understanding of the molecular pathways involved in the intracellular signaling downstream from SLAM could provide treatment targets for these autoimmune diseases.